Utilisation of health services among urban patients who had an ischaemic stroke with different health insurance - a cross-sectional study in China. Issue 10 (10th October 2020) - Yang, Yong; Man, Xiaowei; Nicholas, Stephen; Li, Shuo; Bai, Qian; Huang, Lieyu; Ma, Yong; Shi, Xuefeng
Abstract : Objectives: This study investigates the disparities in the utilisation of patient health services for patients who had a stroke covered by different urban basic health insurance schemes in China. Design: We conducted descriptive analysis based on a 5% random sample from claims data of China Urban Employees' Basic Medical Insurance (UEBMI) and Urban Residents' Basic Medical Insurance (URBMI) in 2015, supplied by the China Health Insurance Research Association. Setting: Chinese urban social insurance system. Participants: A total of 56 485 patients who had a stroke were identified, including 36 487 UEBMI patients and 19 998 URBMI patients. Primary and secondary outcome measures: The primary outcome measures include annual number of hospitalisations, average length of stay (ALOS) and average hospitalisation cost. Out-of-pocket (OOP) cost is the secondary outcome measure. Results: The annual mean number of hospitalisations of UEBMI patients was 1.21 and 1.15 for URBMI patients. The ALOS was significantly longer for UEBMI than for URBMI patients (13.93 vs 10.82, p<0.001). Hospital costs were significantly higher for UEBMI than for URBMI patients (US1724.02 vs US986.59 (p<0.001), while the OOP costs were significantly higher for URBMI than for UEBMI patients (US423.17 vs US407.81 (p<0.001). Patients with UEBMI had higher reimbursement rate than URBMI patients (79.41% vs 66.92%, p<0.001) and a lower self-paid ratio than URBMI patients (23.65% vs 42.89%, p<0.001). Conclusions: Significant disparities were found in the utilisation of hospital services between UEBMI and URBMI patients. Our results call for a systemic strategy to improve the fragmented social health insurance system and narrow the gaps in China's health insurance schemes.